MODEL PMK BERBANTUAN MODUL P2MEL DAN DISPOSISI MATEMATIS DALAM PEMBELAJARAN MATEMATIKA - Nasrullah, Nasrullah; Bernard, Bernard (Indonesian Journal of Educational Studies, 2015)
This study aims to understand how far the influence of model of learning creative prob-lem solving (CPS) supported with P2MeL module toward mathematical disposition of students in senior secondary school, and compared with model of direct teaching (DT). This research is kind of quacy experiment in which students of Jurusan Matematika FMIPA UNM as the research sub-ject. The result of research show that unchangeably mathematical disposition in line with learning model is caused by the lack of students’ activeness getting involved in constructing strategic com-petence. The score of mathematical disposition between CPS supported with P2MeL and DT is in the same of middle category, but the score of DT is 57,89% higher than that of CPS with P2MeL module is 42,11%.